Continuity of care for people with non-psychotic disorders. (February 2013) - Catty, Jocelyn; Cowan, Naomi; Poole, Zoe; Clement, Sarah; Ellis, Gemma; Geyer, Connie; Lissouba, Pascale; Molodynski, Andrew; White, Sarah; Burns, Tom
Background: Service users with non-psychotic disorders are rarely studied. How continuity of care functions for this group is unknown. Aims: To compare users of community mental health teams with non-psychotic disorders to those with psychotic disorders in terms of demographic and illness characteristics, continuity of care and clinical and social functioning. Methods: Service users with non-psychotic disorders ( N = 98) were followed up for one year and compared to 180 service users with psychotic disorders. Continuity of care factors were tested for association with user, illness and service variables. Results: Service users with non-psychotic disorders experienced more care transitions, but there were no differences in team practices in relation to these two different groups. Conclusion: The underlying concepts of continuity of care derived from users with psychotic disorders appear to be meaningful for users with non-psychotic disorders. Their greater likelihood of experiencing disruptive and distressing care transitions needs to be addressed.